2015
DOI: 10.1016/j.euprot.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-centric analysis of the DNA damage response to chemotherapeutic agents in two breast cell lines

Abstract: Please cite this article in press as: Antberg L, et al. Pathway-centric analysis of the DNA damage response to chemotherapeutic agents in two breast cell lines. EuPA Open Proteomics (2015), http://dx.Available online xxx Keywords: DNA repair DNA damage Chemotherapy Breast Cancer Label-free Quantification Pathway-centric analysis Selected reaction monitoring Shotgun proteomics a b s t r a c tThe response to DNA damage by alkylation and DNA topoisomerase inhibition was studied in two breast cancer cells lines. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In agreement, other authors also reported cytotoxicity in the MDA-MB-231 cell line at the same Dox concentration [ 56 ]. Dox cytotoxicity seems to be correlated to the increase of DNA damages and consequently induction of cell death in MDA-MB-231 cells, concordantly with other reports with the same cell line [ 57 , 58 ]. Dox is known for causing DNA damage through several different mechanisms (e.g., DNA intercalation, topoisomerase II inhibition, ROS induction), which can trigger cell cycle arrest, impairment of mitochondrial function and cell death [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 90%
“…In agreement, other authors also reported cytotoxicity in the MDA-MB-231 cell line at the same Dox concentration [ 56 ]. Dox cytotoxicity seems to be correlated to the increase of DNA damages and consequently induction of cell death in MDA-MB-231 cells, concordantly with other reports with the same cell line [ 57 , 58 ]. Dox is known for causing DNA damage through several different mechanisms (e.g., DNA intercalation, topoisomerase II inhibition, ROS induction), which can trigger cell cycle arrest, impairment of mitochondrial function and cell death [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 90%
“…The different mechanisms of these three DDR inhibitors may explain their varying radiosensitizing capabilities. Differences in repair capacity of these cell lines due to variations in other DNA repair genes have been explored in detail elsewhere [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, MCF‐7 cells were found to be more sensitive to catechol than MDA‐MB‐231 cells. Higher DNA repairing efficacies, mutant p53 genotype, condensed chromatin structure, and interactions between extracellular matrix (ECM) to the tumor microenvironment in the MDA‐MB‐231 cells could be among the factors contributing to its chemoresistance (Antberg, Cifani, Levander, & James, 2015; Ramadan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%